2007
DOI: 10.1111/j.1742-7843.2007.00072.x
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium‐Induced Enteropathy in Domestic Cocks: A Biochemical and Histological Study after Subchronic Exposure

Abstract: Abstract:The biochemical and histological sequelae resulting from a diet containing 50.20 mg cadmium/kg were studied in Lohmann brown cockerels from hatching until 30 days of age. The additional cadmium chloride (CdCl 2 ) to the diet induced the formation of lipid peroxides, which via a chain reaction led to accumulation of malondialdehyde in intestinal mucosa. At the end of the study (after 30 days of cadmium exposure) total protein and metallothionein levels in the intestinal mucosa and the relative ileal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…In this study, between 20 and 40 days of contamination, the metal appeared to be unable to efficiently penetrate the intestinal epithelium to reach liver but was still accumulated in muscle. This can be relevant with previous studies that have shown that Cd uptake triggers an inflammatory and secretory response in the small intestines of chickens (Berzina et al 2007). Moreover, Cd dietary contamination with enriched food can impair the efficiency of the metal to penetrate the intestinal epithelium of fish species (Pierron et al 2008).…”
Section: Bioaccumulationmentioning
confidence: 50%
“…In this study, between 20 and 40 days of contamination, the metal appeared to be unable to efficiently penetrate the intestinal epithelium to reach liver but was still accumulated in muscle. This can be relevant with previous studies that have shown that Cd uptake triggers an inflammatory and secretory response in the small intestines of chickens (Berzina et al 2007). Moreover, Cd dietary contamination with enriched food can impair the efficiency of the metal to penetrate the intestinal epithelium of fish species (Pierron et al 2008).…”
Section: Bioaccumulationmentioning
confidence: 50%
“…This toxic metal is known to have various adverse effects on organisms, such as lesions in the kidney or intestinal tissues, induction of reactive oxygen species, DNA damage, impact on hepatic enzymes activities and lipid peroxidation (Mayack et al 1981;Jordan et al 1990;Wang et al 2004;Erdogan et al 2005;Berzina et al 2007). Moreover, Cd impairment on lipid metabolism has also been demonstrated on fish and mammalian species (Pierron et al 2007;Larregle et al 2008).…”
Section: Introductionmentioning
confidence: 95%
“…Damage to intestinal epithelium integrity, including increased paracellular permeability, altered cell viability and inflammatory response, have been reported following exposure to Cd (Duizer et al 1999;Boveri et al 2004;Berzina et al 2007). Cd also favors the production of oxygen species leading to oxidative stress (Wang et al 2004), and induces stress proteins such as MT-IIa, a metal-binding protein, and the heat shock protein HSP70 (Reeves and Rossow 1996;Kiang and Tsokos 1998;Blais et al 1999).…”
Section: Introductionmentioning
confidence: 97%